2020
DOI: 10.1136/bmjopen-2020-037431
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tissue factor in patients with pancreatic cancer: a systematic review protocol

Abstract: IntroductionPancreatic cancer is a highly aggressive digestive system tumour with poor prognosis. Venous thromboembolism (VTE) is a well-known complication of pancreatic cancer, and tissue factor (TF) contributes to the generation of a hypercoagulable state and thrombotic disease in pancreatic cancer. Several studies showed that an elevated TF level was related to the development of VTE and influenced the survival of patients with pancreatic cancer. Thus, we wish to conduct a systematic review of literature to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…In addition to TF levels at registration, we evaluated plasma TF levels at 3, 6, and 12 months in patients with CAT, except for five patients who developed CAT within 3 months after registration. Unlike a previous study 39 on the relationship between VTE and pancreatic cancer, we found that plasma TF levels were not significantly altered during the observation period; the mean changes compared with the values at registration were 1.28, −3.12, and −2.52 pg/mL at 3, 6, and 12 months, respectively (Figure 2D ). Thus, the positive predictive value (23.1%) was not improved, even when the later TF levels were used for estimation.…”
Section: Resultscontrasting
confidence: 97%
“…In addition to TF levels at registration, we evaluated plasma TF levels at 3, 6, and 12 months in patients with CAT, except for five patients who developed CAT within 3 months after registration. Unlike a previous study 39 on the relationship between VTE and pancreatic cancer, we found that plasma TF levels were not significantly altered during the observation period; the mean changes compared with the values at registration were 1.28, −3.12, and −2.52 pg/mL at 3, 6, and 12 months, respectively (Figure 2D ). Thus, the positive predictive value (23.1%) was not improved, even when the later TF levels were used for estimation.…”
Section: Resultscontrasting
confidence: 97%
“…Directly influencing the coagulation profile, especially in the portal blood, is fairly common; however, potentially disturbing the interpretation of this study results in tissue factor (TF) overexpression on the tumor cells [ 13 ]. One of its effects is well described by our D-dimer group with a high concentration in portal blood [ 7 , 14 , 15 , 16 , 17 , 18 ]; however, the other can shorten the aPTT and raise the level of fibrinogen concentration ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies revealed strong correlations of intratumoral heterogeneity in malignant pancreatic lesions with tumor recurrence and survival [8][9][10]. Tumor masses can be quantified non-invasively by using dual-energy computed tomography iodine concentration (DECT-IC) [11,12] or diffusion-weighted magnetic resonance imaging (DWI) based on the random Brownian motion of water molecules within tissues [13]. Radiomics is a quantitative approach that poses the potential to extract a myriad of texture features from medical imaging by using miscellaneous mathematical extraction algorithms.…”
Section: Introductionmentioning
confidence: 99%